Co-doped zigzag graphene nanoribbon based gas sensor for sensitive detection of H2S: DFT study - Ehab Salih (17075206) (2021)
In this work, we present a highly sensitive gas sensor for the detection of poisonous hydrogen sulfide gas (H2S) based on copper and zinc co-doped zigzag graphene nanoribbon (Cu/Zn-ZGNR). The electronic properties as well as the sensing performance of Cu/Zn-ZGNR toward H2S were investigated employing density functional theory (DFT). The adsorption capacity of the newly developed Cu/Zn-ZGNR system was compared with both pristine ZGNR as well as doped Zn-ZGNR and Cu-ZGNR systems. The adsorption energy (Eads) of H2S/Zn-ZGNR and H2S/Cu-ZGNR systems were found to be −2.237 and −1.129 eV, respectively. For the case of H2S/Cu/Zn-ZGNR, the adsorption energy (Eads) and charge transfer (q) reflected an outstanding increase to −7.043 eV and −0.311 e, respectively, when compared with both pristine and doped systems: ZGNR, Zn-ZGNR, and Cu-ZGNR. Moreover, the adsorption distance (D) between H2S and Cu/Zn-ZGNR decreased remarkably to 2.23 Å and an S–Cu bond was generated. The response towards H2S of the developed ZGNR, Zn-ZGNR, Cu-ZGNR, and Cu/Zn-ZGNR gas sensors has been investigated as well. Particularly, the response of H2S to Cu/Zn-ZGNR system demonstrated a significant high value of 48.92%. Therefore, the newly developed co-doped Cu/Zn-ZGNR based gas sensor can be recommended as a highly sensitive H2S Other Information Published in: Superlattices and Microstructures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.spmi.2021.106900